Mesenchymal stem cell-derived exosome mediated long non-coding RNA KLF3-AS1 represses autophagy and apoptosis of chondrocytes in osteoarthritis. Issue 3 (1st February 2022) - Wen, Chuanyang; Lin, Lupan; Zou, Rui; Lin, Fuqing; Liu, Yubao
ABSTRACT: Osteoarthritis is a degenerative joint disease and a leading cause of adult disability. Our previous study has reported that mesenchymal stem cell-derived exosomes (MSC-Exo) mediated long non-coding RNA KLF3-AS1 improves osteoarthritis. This study aims to investigate the molecular mechanism of KLF3-AS1 in osteoarthritis. Chondrocytes were treated with IL-1β to induce chondrocyte injury, followed by MSC-Exo treatment. We found that MSC-Exo enhanced KLF3-AS1 expression in IL-1β-treated chondrocytes. IL-1β treatment reduced cell viability and enhanced apoptosis in chondrocytes. MSC-Exo-mediated KLF3-AS1 promoted cell viability and repressed apoptosis of IL-1β-treated chondrocytes. Rapamycin (autophagy activator) promoted cell viability and suppressed apoptosis of chondrocytes by activating autophagy. Moreover, KLF3-AS1 interacted with YBX1 in chondrocytes. MSC-Exo-mediated KLF3-AS1 activated PI3K/Akt/mTOR signaling pathway, which was abrogated by YBX1 silencing. MSC-Exo-mediated KLF3-AS1 repressed autophagy and apoptosis of chondrocytes by activating PI3K/Akt/mTOR signaling pathway. In conclusion, our data demonstrate that MSC-Exo-mediated KLF3-AS1 inhibits autophagy and apoptosis of IL-1β-treated chondrocyte through PI3K/Akt/mTOR signaling pathway. KLF3-AS1 activates PI3K/Akt/mTOR signaling pathway by targeting YBX1 to improve the progression of osteoarthritis. Thus, this work suggests that MSC-Exo-mediated KLF3-AS1 may be a potential therapeutic target for osteoarthritis.